Ignition dynamics of DME/methane-air reactive mixing layer under reactivity controlled compression ignition conditions: Effects of cool flames. (1st September 2019) - Jin, Tai; Wu, Yunchao; Wang, Xujiang; Luo, Kai H.; Lu, Tianfeng; Luo, Kun; Fan, Jianren
Highlights: Ignition dynamics in turbulent DME/CH4 -air under RCCI condition is studied via DNS. Low-temperature ignition transits to cool flame in the stratified DME/ CH4 -air mixture. High-temperature autoignition is accelerated by the cool flame. The four branches of typical tetrabranchial flames coexist in the field. Abstract: A study of ignition dynamics in a turbulent dimethyl ether (DME)/methane-air mixture under reactivity controlled compression ignition (RCCI) conditions was conducted using direct numerical simulation. Initially, the directly-injected DME and in-cylinder premixed methane-air mixture are partially mixed to form a mixing layer in between. A reduced DME/CH4 oxidization mechanism, consisting of 25 species and 147 reaction steps, is developed and validated. Ignition is found to occur as a two-stage process. Low-temperature autoignition is first initiated in the fuel-rich part of the mixture and then transits to a cool flame, propagating towards the even richer mixture through a balanced reaction-diffusion mechanism. Cool flames not only develop in the mixing layer, but also in the initially stratified DME/methane-air mixture. The formation of high-temperature autoignition kernels is earlier than that in the homogeneous mixture at the same mixture fraction, which is thought to be accelerated by the cool flame. The expanding flames from high-temperature kernels are connected with the neighboring flames before they engulf the stoichiometric mixture iso-lines. The four branches of typical tetrabranchial flames, i.e. cool flame, fuel-rich premixed flame, diffusion flame, fuel-lean premixed flame coexist in the field. The fuel-lean premixed flame branch finally triggers the premixed methane-air flame. The multi-stage and multi-mode nature of the ignition process highlights the intractable challenge to model the RCCI engine combustion.